TRANSPLANTING ENHALUS ACOROIDES (L.F) ROYLE WITH DIFFERENT LENGTH RHIZOME ON THE MUDDY SUBSTRATE AND HIGH WATER DYNAMIC AT BANTEN BAY, INDONESIA - Kiswara, Wawan; Kumoro, Erlangga Dwi; Kawaroe, Mujizat; Rahadian, Nana P. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
This study is a part of transplanting Enhalus acoroides carried out from November 2006 to February 2007 as a compensation of 1.6 ha loss of seagrass beds at Bojonegara, which was facilitated by NGO Rekonvasi Bhumi and funded by oil drilling company, PT Apexindo. The transplanting site was located at Terate, Banten Bay which has muddy substrate with high water dynamic. Healthy transplant seedlings were collected from monospecific vegetation with muddy substrate of donor site at Kepuh. The seedlings of Enhalus have different length of rhizome, 5 and 10 cm, with leaf length of 60 cm and removed roots. Transplanting of Enhalus acoroides was conducted using single shoot seedlings with 9 seedlings per unit in 1 meter square with 5 replicates. Light coefficient (1.17-5.06) and percentage of silt and clay (86.45 ± 2.18 %) at transplant site Terate were both higher than the donor site Kepuh with light coefficient values of 1.21-2.46 and percentage of silt and clay 64.00 ± 5.57 %, respectively. Seedling growth survival of Enhalus acoroides in February 2007 with rhizome length of 10 cm was higher (51.11 ± 25.58%) than seedlings with rhizome length of 5 cm (17.78 ± 18.59%). Leaf length and wide Enhalus acoroides transplants decreased during the study. Water dynamic (waves) influenced light coefficient and turbidity at the transplant site. Field observations showed that mortality of Enhalus acoroides transplants was caused by mud smoothering the leaves and barnacle growing on them. They made the leaves lost their buoyancy, laid on the surface, rotten and finally died. Wave is one of the important physical factor affecting the transplanting seagrass on the muddy substrate.